Determinan Kesejahteraan Keuangan: Peran Mediasi Perencanaan Keuangan - Suryadie, Farach Aliyyah Putri; Lutfi, Lutfi (E-Jurnal Akuntansi; Vol 33 No 2 (2023)DO - 10.24843/EJA.2023.v33.i02.p01, 2023)
Financial well-being is a problem for society in Indonesia today as reflected in the increasing poverty rate in 2021. The study intends to explore the determinants of financial well-being which include internal locus of control, financial experience, financial planning, and demographic factors of marital status. This study aims to determine the role of financial planning in mediating the effect of financial experience on financial management and to what extent marital status moderates the mediated relationship. The research sample is 160 families living in the cities of Surabaya, Sidoarjo and Gresik. Hypothesis testing was carried out using partial least squares structural equation modeling (PLS-SEM). The results of the study prove that locus of internal control, financial experience, financial planning, and marital status significantly increase financial well-being. The research findings also prove that financial planning mediates the effect of financial experience on financial well-being. Research implies the importance of someone to carry out financial planning earlier, be more able to control themselves, and increase experience related to financial products in order to improve financial well-being. Keywords: Financial Well-Being; Financial Planning; Internal Locus of Control; Financial Experience; Marital Status